Open plains are not a level playing field for hominid consonant-like versus vowel-like calls - Charlotte Gannon; Russell A. Hill; Adriano R. Lameira (Scientific Reports, 2023)
Abstract Africa’s paleo-climate change represents an “ecological black-box” along the evolutionary timeline of spoken language; a vocal hominid went in and, millions of years later, out came a verbal human. It is unknown whether or how a shift from forested, dense habitats towards drier, open ones affected hominid vocal communication, potentially setting stage for speech evolution. To recreate how arboreal proto-vowels and proto-consonants would have interacted with a new ecology at ground level, we assessed how a series of orangutan voiceless consonant-like and voiced vowel-like calls travelled across the savannah. Vowel-like calls performed poorly in comparison to their counterparts. Only consonant-like calls afforded effective perceptibility beyond 100 m distance without requiring repetition, as is characteristic of loud calling behaviour in nonhuman primates, typically composed by vowel-like calls. Results show that proto-consonants in human ancestors may have enhanced reliability of distance vocal communication across a canopy-to-ground ecotone. The ecological settings and soundscapes experienced by human ancestors may have had a more profound impact on the emergence and shape of spoken language than previously recognized.